Retrospective analysis of lithium treatment: examination of blood levels - Uskur, Tuğçe; Güven, Oya; Tat, Mustafa (Frontiers in Psychiatry, 2024)
Introduction Lithium is a key medication for treating various neuropsychiatric disorders, with a narrow therapeutic index and significant drug interactions. Monitoring lithium blood levels is crucial. This study aims to investigate the relationship between lithium blood levels and demographic characteristics such as age and gender, as well as possible drug interactions, in patients with a history of lithium use who applied to various services and outpatient clinics. Materials & methods The files of 438 patients who were admitted to various services and outpatient clinics of Kırklareli Training and Research Hospital between January 1 and December 31, 2023, were retrospectively reviewed. Patients’ blood lithium levels, gender, age, service/outpatient clinic they admitted to, other medications used, urea, creatinine, and eGFR values were recorded. Results When the demographic characteristics of 438 patients were examined, 62% were female (270), 38% were male (168), and the average age was 46.3 ± 14.8 years, showing a normal distribution. It was found that 192 patients (71 males, 121 females) had therapeutic lithium blood levels, while 244 patients (97 males, 147 females) had levels below 0.6 mmol/L. Two female patients had blood levels above the therapeutic range (1.23 and 1.43 mmol/L). Among the clinics and services, the four most frequented were the psychiatry clinic (314 patients), internal medicine clinic (36 patients), emergency service (27 patients), and medical oncology clinic (17 patients). Of the 314 patients admitted to the psychiatry clinic, 168 had therapeutic drug levels; only 7 of the 36 admitted to internal medicine had therapeutic levels; 12 of the 27 patients in the emergency service had therapeutic levels; and all 17 patients in medical oncology had levels below therapeutic limits. Discussion The data emphasize the importance of regular blood level monitoring to ensure lithium treatment’s efficacy and patient safety. It is noteworthy that most patients in the psychiatry clinic had therapeutic drug levels, while those in other clinics had lower levels. Conclusion In conclusion, this study highlights the importance of regular blood level monitoring to ensure the efficacy and safety of lithium treatment.